Alterations in gut microflora populations and brush border functionality following intra-amniotic administration (Gallus gallus) of wheat bran prebiotic extracts. Issue 8 (19th July 2019) - Wang, Xuan; Kolba, Nikolai; Liang, Jianfen; Tako, Elad
Abstract : Wheat bran is the by-product of milling wheat flour which is one of the richest sources of dietary fiber, and cellulase that can be used for increasing the soluble dietary fiber. Abstract : Wheat bran is the by-product of milling wheat flour which is one of the richest sources of dietary fiber, and cellulase that can be used for increasing the soluble dietary fiber. We hypothesize that wheat bran prebiotics would improve mineral-metabolism gene expression, and intestinal functionality, and increase health-promoting bacterial populations in vivo ( Gallus gallus ). By using the intra-amniotic administration procedure, five groups (non-injected; 18 Ω H2 O; 100 mg mL −1 wheat bran prebiotics; 100 mg mL −1 cellulase wheat bran prebiotics; 50 mg mL −1 Arbinose) were utilized. Upon hatch, the cecum, small intestine and liver were collected for assessment. The results indicated that wheat bran prebiotics significantly up regulated the expression of certain brush border membrane functional genes, and mineral metabolism related proteins, in addition to increasing the intestinal beneficial bacterial populations. Prebiotics from wheat bran, cellulase wheat bran and arabinose increased the intestinal villi height, and goblet cell diameters and numbers.